MODEL PENGEMBANGAN LAYANAN BIMBINGAN DAN KONSELING DALAM MEMBENTUK TINGKAH LAKU REMAJA BAGI ORANG TUA TIPE PERMISIF - Fitria Kasih (Universitas PGRI SUMATERA BARAT, 2017)
The purpose of this study was to describe: 1) the representation of permissive parents in shaping adolescent's behavior. 2) the impact of permissive parents in shaping adolescent's behavior. 3) the developmental model of guidance and counseling services in shaping adolescent's behavior as a result of the permissive parenting. This study was descriptive qualitative approach. The key informants were two parents, two teenagers with one of their sister. The instrument used was structured interview and technique of data analysis was data reduction, data presentation and conclusion inductively. The results showed that: 1) the representation of permissive parents in shaping adolescent's behavior; it strongly needs to give them freedom to do many things without control and guidance. 2) the impact of permissive parents in shaping adolescent's behavior was they frequently use the freedom given without responsibility. 3) the developmental model of guidance and counseling services in shaping adolescent's behavior as a result of the permissive parenting was using an improved communication model and implementing counseling reality. The implication of this study is to apply the various types of parenting so that the control and guidance have a good impact for the adolescents. Furthermore, parents need to give the adolescents freedom in order to develop their positive behavior.Keywords: Guidance and Counseling Services, Adolescents’ Behavior, Parents’ Permissive Model